2017
DOI: 10.22159/ijcpr.2017.v9i3.19599
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Phytochemical Screening and in Vitro Antimicrobial Activity of Ethanolic Extract of Stem of the Herb Basella Alba L. Var Rubra (L.) Stewart (Family-Basellaceae)

Abstract: Objective: To evaluate the antimicrobial activity ethanolic extracts of Basella alba L. var. rubra (L.) stewart (family-basellaceae) along with phytochemical analysis. Methods:The ethanolic extract of stems of the herb Basella alba L. var. rubra (L.) stewart (family-basellaceae) were prepared and analysed for phytochemical constituents using standard methods. The antimicrobial activity of the plant extracts were examined against 2 bacterial strains among one is gram positive and other is gram negative and2 fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Recent reports on B. alba betacyanins [ 2 , 3 , 4 , 5 , 6 , 17 , 23 , 24 , 25 ] focused on the main pigment, gomphrenin, only scarcely mentioning some other acylated gomphrenins which were structurally identified two decades ago as the principal acylated pigments in purple Gomphrena globosa L. [ 7 , 29 ]. In this study, our detailed studies evidently detected new betacyanin pigments ( Table 1 , Figure 2 ) and also revealed completely novel structures with unique acylation patterns ( Table 2 and Table 3 ) as well as compared quantitatively the two plant varieties ( Section 2.7 ) [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports on B. alba betacyanins [ 2 , 3 , 4 , 5 , 6 , 17 , 23 , 24 , 25 ] focused on the main pigment, gomphrenin, only scarcely mentioning some other acylated gomphrenins which were structurally identified two decades ago as the principal acylated pigments in purple Gomphrena globosa L. [ 7 , 29 ]. In this study, our detailed studies evidently detected new betacyanin pigments ( Table 1 , Figure 2 ) and also revealed completely novel structures with unique acylation patterns ( Table 2 and Table 3 ) as well as compared quantitatively the two plant varieties ( Section 2.7 ) [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Traditional medicine, especially in India and China, uses different parts of said plants to treat many diseases [ 2 ]. In addition to the content of vitamins and minerals, the extracts of these plants can be attributed to antimicrobial, [ 3 ] anti-inflammatory and antidepressant properties [ 2 ]. Valuable sources of pro-health substances are both the stems and leaves of Malabar spinach [ 4 ], but also extracts from its fruits, which have been proven, among others, to show cytotoxic properties against human cervical cancer cells [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mobile phases were A, 2% formic acid in water and B, methanol. The gradient profile was (t (min), % B), (0, 10), (12,40), (15,80), (19,80). The full-range PDA signal was recorded, and individual chromatograms were displayed at 538, 505, 490, and 440 nm.…”
Section: Chromatographic Analysis With Detection By a Low-resolution ...mentioning
confidence: 99%
“…17 These plants are primarily cultivated in subtropical regions, where their potent health benefits have been acknowledged and well-regarded. 18 Their anti-inflammatory and antibacterial properties are highlighted, 19 but studies have also reported the cytotoxic effect of Malabar spinach fruit extracts on human cervical carcinoma cells. 20 Besides containing compounds such as carbohydrates, proteins, lipids, niacin, ascorbic acid, and tocopherols, Malabar spinach is also a rich source of betalain pigments.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the standard drug gentamycin showed 29 and 23mm Zone of inhibition respectively at 20mg/ml. The maximum antifungal activity was also observed at 100mg/ml concentration i.e., 20.2 and 15.25mm zone of inhibition and standard drug fluconazole at concentration of 20mg/ml showed 24 and 22mm zone of inhibition against Candida albicans and Trichophyton rubrum respectively [20]. evaluated antimicrobial activity of B. alba fruit using agar well diffusion method against eight species of microorganisms.…”
mentioning
confidence: 92%